Once-Daily Extended-Release Levetiracetam Improves Medication Compliance in Adolescent Epilepsy Patients - Seung Yeon Jung; Yoon Young Yi; Joon Won Kang (Korean Child Neurology Society, 2021)
Purpose Since pharmacologic agents are the mainstay of epilepsy treatment, drug compliance is one of the most important factors in seizure control. Once-daily levetiracetam (LEV) has been proven to have the same efficacy as that of an immediate-release (IR) formulation. A reduced number of doses may improve drug compliance and patient satisfaction. The aim of this study was to assess drug compliance and patient satisfaction when changing from IR to an extended-release (ER) formulation. Methods Adolescent patients diagnosed with epilepsy who were taking LEV from 2018 to 2020 were included in this study. Compliance charts were reviewed retrospectively. We compared the frequency of seizure occurrence with the frequency of skipping doses and adverse effects before and after changing formulations. Changes in subjective compliance and satisfaction were also investigated. Results Among 585 patients taking LEV, 44 were included in this study. The average age of the included patients was 16.4±2.0 years. There was no significant change in the average seizure frequency (P=0.491) after switching formulations. Objective compliance based on chart records significantly improved after switching formulations (P=0.021). Additionally, 26 of 44 patients mentioned how they felt about switching formulations, of whom 25 (96.2%) were satisfied with the ER formulation. Thirteen of 24 patients (54.2%) reported better compliance. Conclusion Our study shows that the efficacy of LEV ER was similar to that of the IR formulation. The reduced number of medication doses improved patient satisfaction and medication compliance. LEV ER may be preferable in adolescent epilepsy patients.